PERKIRAAN PERMINTAAN PENUMPANG BANDAR UDARA BARU DI KEDIRI - Dwi Ardianta Kurniawan; Juhri Iwan Agriawan; Hengki Purwoto (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2020)
Abstract This study aims to develop a method of calculating the passenger demand for new airport in Kediri, using secondary data, as part of the pre-feasibility study stage. The zone approach model is used in this study. The modeling results show that the potential passengers of the new Kediri Airport are between 571 thousand passengers, for the pessimistic scenario, up to 1.4 million passengers, for the optimistic scenario in 2020. The results of this study are quite realistic when compared to the potential passengers at similar airports in Malang, East Java Province. Keywords: airport; passenger; passenger demand; potential passengers. Abstrak Kajian ini bertujuan untuk mengembangkan metode perhitungan permintaan penumpang bandar udara baru di Kediri, dengan memanfaatkan data sekunder, sebagai bagian tahapan prastudi kelayakan. Model zone approach digunakan pada kajian ini. Hasil pemodelan memperlihatkan bahwa potensi penumpang bandar udara baru Kediri adalah antara 571 ribu penumpang, untuk skenario pesimis, hingga 1,4 juta penumpang, untuk skenario optimis pada tahun 2020. Hasil kajian ini cukup realistis bila dibandingkan dengan potensi penumpang di bandar udara sejenis di Malang, Provinsi Jawa Timur. Kata-kata kunci: bandar udara; penumpang; permintaan penumpang; potensi penumpang.